2015
DOI: 10.1164/rccm.201408-1509oc
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Protein Receptor Type II Deficiency and Increased Inflammatory Cytokine Production. A Gateway to Pulmonary Arterial Hypertension

Abstract: Rationale: Mutations in bone morphogenetic protein receptor type II (BMPR-II) underlie most cases of heritable pulmonary arterial hypertension (PAH). However, disease penetrance is only 20-30%, suggesting a requirement for additional triggers. Inflammation is emerging as a key disease-related factor in PAH, but to date there is no clear mechanism linking BMPR-II deficiency and inflammation.Objectives: To establish a direct link between BMPR-II deficiency, a consequentially heightened inflammatory response, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
111
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 127 publications
(116 citation statements)
references
References 61 publications
5
111
0
Order By: Relevance
“…However, the exact contribution of either ROS sources to PH development remains to be elucidated. The importance of prooxidative metabolism in PH is supported by studies where suppression of oxidative metabolism, including the use of tempol, leads to the reduction of PH development (24)(25)(26)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact contribution of either ROS sources to PH development remains to be elucidated. The importance of prooxidative metabolism in PH is supported by studies where suppression of oxidative metabolism, including the use of tempol, leads to the reduction of PH development (24)(25)(26)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly there is increasing evidence, suggesting a link between mutations in the BMPR2 gene, which is associated with an increased risk for PAH, and inflammation. Recently it has been reported that BMPR2 deficiency increases the LPS stimulated lung and circulatory IL-6 and IL-8 production, in patients with BMPR2 deficiency as compared to control subjects (125). In an earlier study it was shown that there is a negative feedback loop between IL-6 and BMPR2 signaling, both in vitro and in vivo.…”
Section: Pulmonary Hypertension and Inflammationmentioning
confidence: 99%
“…43,44 Future studies should also address the role of NETs in the pathogenesis of PH and investigate whether neutrophils from PAH and CTEPH patients show increased propensity to form NETs. This would not be entirely unexpected because PAH and CTEPH neutrophils respond to stimulation with increased inflammatory mediator generation ex vivo, including increased respiratory burst, elastase secretion, and lipid mediator synthesis.…”
Section: Pad4mentioning
confidence: 99%